INORGANIC ARSENIC SPECIATION IN THE ATMOSPHERE: STUDY IN ISFAHAN - A KALANTARI (Journal of Research in Medical Sciences, 2000)
Introduction. Arsenic is one of the most hazardous elements that associate with airborne particulate matter in the atmosphere. Among the different species of arsenic, ASIII has the most toxic and carcinogenic property between any other kind of this element. Arsenic speciation is important in environmental studies.
Methods. We collected 59 samples of airborne particulate matter from the atmosphere in Isfahan in a three months period by a high volume air sampler with a flow rate of 1 m3 min-1. Air particulates were collected on the paper filter (Whatman No.41). Four different digestive procedures were examined in order to find the best method. At last we chose digestion of filter with HCI (10-4N) due to its feasibility, cost benefit and efficacy. Other methods that examined were digestion of filter with a mixture of HN03 and H2O2, with a mixture of HNO3 and H2O2 and with HCI (1 N). The determination of As3+ and As5+ concentrations were performed by hydrIde generation atomic absorption spectrometry. The effect of Ph on the absorption signal was also investigated in arsenic speciation.
Results. Average of total saspended particles (TSP) in July, August, and September 1998 were 223, 172, and 247 mg.m3 respectively. The recovery of arsenic from airborne particulate matter was almost the same for the different digestion methods. The concentration and volume of NaBH4 was optimized for determining of different species of arsenic. At pH=5, Asv didn't produce any absorption signal. So, the determination of ASm was carried out easilyat the above mentioned pH.
The concentrations of total arsenic were determined in 47 samples. The mean concentrations of total arsenic in July, August and September were 3.31, 2.01 and 2.6, respectively.
Discussion. More than 50 percent of total atmospheric arsenic exists as ASIII which is the most toxic and carcinogenic forms of this element. So, it is recommended to make a suitable policy for decreasing of this hazardous pollution in our environment.